2021
DOI: 10.1063/5.0061571
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning-based design of broadband GHz complex and random metasurfaces

Abstract: We are interested in exploring the limit in using deep learning (DL) to study the electromagnetic (EM) response for complex and random metasurfaces, without any specific applications in mind. For simplicity, we focus on a simple pure reflection problem of a broadband EM plane wave incident normally on such complex metasurfaces in the frequency regime of 2–12 GHz. In doing so, we create a DL-based framework called the metasurface design deep convolutional neural network (MSDCNN) for both forward and inverse des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 72 publications
1
28
0
Order By: Relevance
“…If this goal is met, we will consider that the DL model is successful, which may be able to capture the underlying physics. Unfortunately, we have concluded in a recent study [44] that current CNN based DL models are insufficient to reach this optimal condition for which cross classes forward prediction shows deteriorating performance. We postulate that this is due to non-optimal neural architecture adopted, which motivates us to share our dataset in this paper with other researchers for future improvements.…”
Section: Relationship Between Classesmentioning
confidence: 93%
See 4 more Smart Citations
“…If this goal is met, we will consider that the DL model is successful, which may be able to capture the underlying physics. Unfortunately, we have concluded in a recent study [44] that current CNN based DL models are insufficient to reach this optimal condition for which cross classes forward prediction shows deteriorating performance. We postulate that this is due to non-optimal neural architecture adopted, which motivates us to share our dataset in this paper with other researchers for future improvements.…”
Section: Relationship Between Classesmentioning
confidence: 93%
“…Fourier transform [23,47], discrete cosine transform, wavelet transform and uniform downsampling are some popular options in constructing compressed representations. In our prior work [44], we reported that uniform down-sampling has produced good results to predict the magnitude. However, the phase spectra are oscillatory due to the periodicity of 2π.…”
Section: Magnitude and Phase Spectrummentioning
confidence: 96%
See 3 more Smart Citations